Treating amyloid transthyretin cardiomyopathy: lessons learned from clinical trials - Tomasoni, Daniela; Bonfioli, Giovanni Battista; Aimo, Alberto; Adamo, Marianna; Canepa, Marco; Inciardi, Riccardo M.; Lombardi, Carlo Mario; Nardi, Matilde; Pagnesi, Matteo; Riccardi, Mauro; Vergaro, Giuseppe; Vizzardi, Enrico; et al. (Frontiers in Cardiovascular Medicine, 2023)
An increasing awareness of the disease, new diagnostic tools and novel therapeutic opportunities have dramatically changed the management of patients with amyloid transthyretin cardiomyopathy (ATTR-CM). Supportive therapies have shown limited benefits, mostly related to diuretics for the relief from signs and symptoms of congestion in patients presenting heart failure (HF). On the other hand, huge advances in specific (disease-modifying) treatments occurred in the last years. Therapies targeting the amyloidogenic cascade include several pharmacological agents that inhibit hepatic synthesis of TTR, stabilize the tetramer, or disrupt fibrils. Tafamidis, a TTR stabilizer that demonstrated to prolong survival and improve quality of life in the ATTR-ACT trial, is currently the only approved drug for patients with ATTR-CM. The small interfering RNA (siRNA) patisiran and the antisense oligonucleotide (ASO) inotersen have been approved for the treatment of patients with hereditary ATTR polyneuropathy regardless of the presence of cardiac involvement, with patisiran also showing preliminary benefits on the cardiac phenotype. Ongoing phase III clinical trials are investigating another siRNA, vutrisiran, and a novel ASO formulation, eplontersen, in patients with ATTR-CM. CRISPR–Cas9 represents a promising strategy of genome editing to obtain a highly effective blockade of TTR gene expression.